2007
DOI: 10.1583/06-2007.1
|View full text |Cite
|
Sign up to set email alerts
|

Aortic Neck Dilatation and Endograft Migration Are Correlated With Self-Expanding Endografts

Abstract: Aortic neck dilatation following endovascular AAA repair appears to be correlated with self-expanding endografts, which may contribute to a higher incidence of graft migration compared to that occurring with balloon-expandable endografts.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
46
0
2

Year Published

2009
2009
2019
2019

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(49 citation statements)
references
References 13 publications
1
46
0
2
Order By: Relevance
“…The radial force and lack of effective transmural fixation that characterize most endograft technologies today are largely responsible for the late complications related to migration and proximal neck dilatation. 4,6,14,15 Irrespective of the design, 16,17 any endostapling or independent endovascular fixation technology that allows the operator to securely attach a graft or other device to the load-bearing portion of the vascular wall, the adventitia, has the potential to change the nature of endovascular aortic grafting and potentially a variety of other endovascular procedures and devices. In addition to the secure attachment of the graft to the wall, the design of the helical EndoStaples described in this report have the potential to secure the aortic wall to the graft thus preventing one of the most insidious late complications of aortic aneurysm repair, namely continued aortic dilation at the proximal attachment site.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The radial force and lack of effective transmural fixation that characterize most endograft technologies today are largely responsible for the late complications related to migration and proximal neck dilatation. 4,6,14,15 Irrespective of the design, 16,17 any endostapling or independent endovascular fixation technology that allows the operator to securely attach a graft or other device to the load-bearing portion of the vascular wall, the adventitia, has the potential to change the nature of endovascular aortic grafting and potentially a variety of other endovascular procedures and devices. In addition to the secure attachment of the graft to the wall, the design of the helical EndoStaples described in this report have the potential to secure the aortic wall to the graft thus preventing one of the most insidious late complications of aortic aneurysm repair, namely continued aortic dilation at the proximal attachment site.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to the secure attachment of the graft to the wall, the design of the helical EndoStaples described in this report have the potential to secure the aortic wall to the graft thus preventing one of the most insidious late complications of aortic aneurysm repair, namely continued aortic dilation at the proximal attachment site. 4,14,15 The discrete nature of EndoStaples al- …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…6 As a result of oversizing, recent reports documented relevant neck dilatation rates of 28% and migration of the devices in 25% of cases for SES. 10 Alternative implantation devices using a BES presented several advantages, such as exact deployment and good results in early-term and long-term follow-up. 4,6,7,10,11 Malas et al 6 presented data from the Montefiore Endografting System (MEGS), with an encouraging absence of neck dilatation and graft migration in their series.…”
Section: Discussionmentioning
confidence: 99%
“…13 Neck enlargement has been related to the degree of stent graft oversizing at the time of implantation 7,14,15 and has been implicated in device migration and the development of new-onset type I endoleaks. 5,11,12,16,17 Although absence of aortic neck dilatation has been reported in patients treated with balloonexpandable stent (BES) grafts, 18,19 systematic reviews have found no clear association between neck dilation and SES grafts 15 and have concluded that aortic neck dilation is most probably an expression of ongoing aneurysm wall degeneration of the infrarenal aortic segment. 20 The Nellix device (Endologix, Irvine, Calif), a novel endograft that uses BESs rather than SESs, along with polymer-filled endobags, to achieve fixation and seal of the aneurysm sac, has experienced favorable early clinical results.…”
mentioning
confidence: 99%